2021
DOI: 10.3390/jfb12030042
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties, Surface Microhardness, and Dentin Shear Bond Strength of Resin-Modified Glass Ionomer Cements Containing Methacrylate-Functionalized Polyacids and Spherical Pre-Reacted Glass Fillers

Abstract: The aim of this study was to prepare experimental resin-modified glass ionomer cements (RMGICs) containing low levels of hydroxyethyl methacrylate (HEMA) for pulp protection. Liquid and powder phases of the experimental RMGICs were polyacid functionalized with methacrylate groups and spherical pre-reacted glass fillers (SPG). Two types of liquid phase containing 0 wt. % HEMA (CM liquid) or 5 wt. % HEMA (CMH liquid) were formulated. The experimental RMGICs were prepared by mixing SPG fillers with CM liquid (F1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A previous study successfully prepared resin-modified glass ionomer cements containing polyacid functionalized with methacrylate groups [ 21 ]. The use of different liquid phases containing HEMA (0 or 5 wt%) showed negligible effects on the rheological properties, surface microhardness, and shear bond strength to dentin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study successfully prepared resin-modified glass ionomer cements containing polyacid functionalized with methacrylate groups [ 21 ]. The use of different liquid phases containing HEMA (0 or 5 wt%) showed negligible effects on the rheological properties, surface microhardness, and shear bond strength to dentin.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because the HEMA enhanced water sorption, plasticizing the polymer network and thus reducing the strength and modulus of the elasticity of the materials [ 51 ]. A previous study demonstrated that F1 and F2 showed higher surface microhardness than VB [ 21 ]. However, the biaxial flexural strength of VB was comparable with that of F1 but higher than that of F2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations